MACROSCOPIC ANATOMY OF THE FORELIMB MUSCULATURE IN THE WHITE FRONTED CAPUCHIN MONKEY (CEBUS ALBIFRONS) - Cribillero Ch., Nelly (2009)
The objective of the present study was to identify and describe the muscular structures of the forelimb of the white fronted capuchin (Cebus albifrons). Four male adult specimens were used. The standard techniques for embalming were used and the dissection of the muscles was made in the lateral and medial side of the forelimb. It is described 42 muscles, of which six muscles were in the shoulder girdle, six muscles in the region of the upper arm, 19 muscles in the region of the forearm where 11 were located in the lateral side and eight in the medial side, and 11 muscles in the region of the hand.